The impact of culturally-informed messages to reduce sugar-sweetened beverage consumption: An experiment among Black women in the United States. - Rhyan N Vereen; Marissa G Hall; Francesca Dillman Carpentier; Rachel W Goode; Seth M Noar; Allison J Lazard (PLoS ONE)
Objective Sugar-sweetened beverage (i.e., sugary drink) consumption is associated with chronic health issues that disproportionately affect Black women. Culturally-informed (CI) health campaigns may be more effective among Black women than campaigns designed for general audiences. This study assesses the effects of a CI campaign on consumption intentions, comparing these effects to general audience and control campaigns. Methods We conducted an online between-persons randomized experiment with a national convenience sample of 502 Black women in February 2023. Participants were randomly assigned to view a CI, general audience, or control campaign. Outcomes were intentions to decrease sugary drink consumption (primary outcome; range 1-7), knowledge of (range 0-4) and perceived susceptibility to health harms (range 1-5) and sharing intentions (range 0-3). Results The CI campaign had significantly higher perceived cultural relevance (M = 4.61) than the general audience (M = 3.64) or control (M = 3.66; p's<0.05) campaigns. Consumption intentions did not differ by campaign condition (F = 0.03, p>0.05). There was no main effect of campaign condition on knowledge or perceived susceptibility (p's>0.05), though findings were moderated by body size. Based on body size, women reported less perceived susceptibility or knowledge when exposed to the CI campaign, compared to either the control or general audience campaign. Sharing intentions did not differ by campaign condition. Conclusions Future research should continue to examine the role of refining message content over a longer duration to understand whether the anticipated impact of CI messages can be achieved in the context of sugary drink consumption among Black women.